2019
DOI: 10.1371/journal.pmed.1002902
|View full text |Cite
|
Sign up to set email alerts
|

Determination of birth-weight centile thresholds associated with adverse perinatal outcomes using population, customised, and Intergrowth charts: A Swedish population-based cohort study

Abstract: BackgroundAlthough many studies have compared birth-weight charts to determine which better identify infants at risk of adverse perinatal outcomes, less attention has been given to the threshold used to define small or large for gestational age (SGA or LGA) infants. Our aim was to explore different thresholds associated with increased risk of adverse perinatal outcomes using population, customised, and Intergrowth centile charts.Methods and findingsThis is a population-based cohort study (Swedish Medical Birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 27 publications
(30 reference statements)
6
43
0
3
Order By: Relevance
“…A possible solution is to use a prescriptive birthweight standard, such as those produced by INTERGROWTH-21 st , to audit care. However our findings, and those of others [21][22][23][24][25], give reason to be cautious of this approach too. We found that the normative INTERGROWTH-21 st birthweight distribution is left-shifted compared to Australian population centiles, yielding a much lower proportion of babies with birthweight <3 rd and <10 th centile.…”
Section: Plos Onesupporting
confidence: 64%
“…A possible solution is to use a prescriptive birthweight standard, such as those produced by INTERGROWTH-21 st , to audit care. However our findings, and those of others [21][22][23][24][25], give reason to be cautious of this approach too. We found that the normative INTERGROWTH-21 st birthweight distribution is left-shifted compared to Australian population centiles, yielding a much lower proportion of babies with birthweight <3 rd and <10 th centile.…”
Section: Plos Onesupporting
confidence: 64%
“…During the last decade, several international growth standards have been created 5 8 . However, doubts have been raised regarding the applicability of these international standards when evaluated in different populations 7 , 9 11 . It has therefore been advised that the international standards should be evaluated in each separate population before taken into general practice 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Birth year was categorized as 1995–1999, 2000–2004, 2005–2009, 2010–2014, and 2015–2016 and maternal age at birth was categorized as <20, 20–24, 25–29, 30–34, 35–39, and ≥40 years [ 35 ]. To adjust for differences in birth weight, sex-specific size for GA was calculated as “small for GA” (below or equal to the 10th percentile), “appropriate for GA” (between the 11th and 90th percentile), and “large for GA” (above the 90th percentile) [ 36 ]. Sex-specific percentiles for each gestational week were calculated within each country, using the observed birth weights as the reference.…”
Section: Methodsmentioning
confidence: 99%
“…RR of ASD increased by GA, from 40 to 24 weeks and from 40 to 44 weeks of gestation. The RR of ASD in children born in weeks [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], and 43-44 compared to weeks 37-42 were estimated at 2.31 (95% confidence interval [CI] 2.15-2.48; 1.67% vs 0.83%; p-value < 0.001), 1.35 (95% CI 1.30-1.40; 1.08% vs 0.83%; p-value < 0.001), and 1.37 (95% CI 1.21-1.54; 1.74% vs 0.83%; p-value < 0.001), respectively. The main limitation of this study is the lack of data on potential causes of pre-or postterm birth.…”
mentioning
confidence: 99%